Native bacteria for field biocontrol of black root rot in Egyptian strawberry - Abd-El-Kareem, Farid (2023)
Increasing cultivation of strawberry in Egypt has boosted efforts to increase its yield. Biocontrol agents (BCAs) may avoid side effects and health risks caused by chemical fungicides used to control black root rot disease in strawberry. Some BCAs control the disease and augment strawberry yield, but additional research is needed to fit BCAs into emerging control strategies. The impact of six bacterial isolates of Paenibacillus polymyxa and Bacillus brevis on this disease and on berry yield is reported and compared to a common chemical fungicide.